Phenotypic and Molecular Characterization of Pasteurella Multocida Obtained From Poultry in Iran - Jabbari, Ahmad Reza (2001)
A collection of twenty five Pasteurella multocida isolates obtained from avian pasteurellosis in northern part (endemic area) of Iran were studied for some of their phenotypic and molecular characteristics. This research is the first study on conducting of serotyping and molecular characterization of avian P.multocida in Iran. Based on the biochemical characteristics, all P.multocida isolates tested belonged to subspecies (biotype) multocida. Antimicrobial sensitivity test showed that all the isolates examined were resistant to at least three of the thirteen antimicrobials tested. Among the antimicrobial agents, chloramphenicol, combination of sulfametoxazin and trimetoprim and nitrofurantoin were found to be the most effective (100% sensitivity) followed by tetracycline (96% sensitivity), penicillin (88% sensitivity) and gentamycin (76% sensitivity). The highest percentage of resistance was found against lincomycin, bacitracin and cloxacillin (100% resistant) followed by furazolidone and colistin (84% and 68% respectively). Agar gel diffusion precipitation (AGDP) test was used to determine somatic serotypes of the isolates. According to the results of the AGDP test, Serotype 1 was dominant among avian isolates from endemic area. Serotypes 3, 3 x 4 and 4, found for the first time in the country were also identified among the isolates. Electrophoresis protein patterns of the isolates were studied by using sodium dodecyl sulphate polyacylamide gel (SDS-PAGE). All strains were similar in the majority of protein bands. The main difference between protein patterns of the isolates was revealed in the position of one of the major band (H Protein) presented in the 34-38 KDa region. According to H protein position, three distinguishable groups were identified. In protein type I, the molecular mass of H protein was about 38 KDa but in protein types II and III it was 36.5 and 34 KDa respectively. The minimum lethal dose (MLD) of the strains with protein types I, II and III as a virulence determinant was identified in mice. It was revealed that the strain with protein type III had the least virulence and the strain with protein type I had the greatest virulence in mice. Immunization of mice with strain PMI030 (protein type I) induced a good protection against homologous protein type challenge. Restriction enzyme analysis (REA) of chromosomal DNA and repetitive extragenic palindromic elements peR (REP-peR) were used for determination of genetic diversity among the isolates. DNA fingerprinting by Hpall digestion divided the twenty-five isolates into 7 REA groups, 2 of which contained a single isolate. DNA fingerprinting with REP-peR revealed a great genetic diversity among the isolates. According to amplified DNA patterns, a total of 9 REP-peR groups were determined. REP-peR produced amplified bands ranging in size from approximately 700 bp to 3.6 Kb with two species-specific bands of 0.8 Kb and 2.3 Kb. REP-peR was able to differentiate P.multocida isolates from different source and geographical areas. Results of this study showed that the use of REP element amplification by polymerase chain reaction is highly reproducible and can be suggested as a suitable epidemiologic tool especially for investigation on the origin of outbreaks and similarity between different avian isolates of P. multocida.